Breaking the Chains, Embracing the Earth: A Study on Shiva’s Staying Alive: Women, Ecology and Survival in India and Plumwood’s Feminism and Mastery of Nature - Dhungel, Thakur Prasad (Far Western Review, 2024)
This is an article on literary criticism. It explores eco feminist literary criticism by analyzing two lines of critics led by Vandana Shiva and Val Plum wood. Shiva shows that there is some connection between the destruction of nature and the oppression of women. For her, it is capitalistic consumerism that is the root cause of this exploitation. Women and nature both have nurturing qualities, and they should be understood in this way so that they can fight against the patriarchal capitalist framework. Contrary to this, Plum wood opines that connecting women and nature as nurturing things is the patriarchal formation of discourse that keeps men at a superior level and women and nature at an inferior level. This is the creation of binary opposition or dualism and this discourse should be rejected. In these two lines of discourse, the paper will explore the differences in their line of thinking and the point of consensus in eco feminist literary criticism. With this, the article concludes with the idea that the chain created by traditional patriarchal exploitative binary system should be broken by establishing a new earth centered system based on egalitarianism where both women and men work together with nature in harmony.